Keanekaragaman dan Kemelimpahan Burung Pemangsa (Raptor) Migran di Kawasan Bukit 76 Kaliurang, Yogyakarta - Giry Xavira Putri; Bambang Agus Suripto; Asman Adi Purwanto (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2021)
Migratory birds are birds that fly or move from their breeding place to their non-breeding location. Migratory birds usually migrate to the southern part of the earth or tropical regions to avoid limited resources during winter in their breeding areas (Bildstein, 2006). Bird of Prey or Raptors are a group of birds that frequently migrate. Raptors carry out-migration in several areas which are commonly referred to as flyways. Indonesia is also part of the flight path for migratory birds (Sukmantoro et al., 2007). At this time there were approximately 17 types of migrant raptors in Indonesia. Research on raptor migration has been carried out for a long time in various regions. In the Yogyakarta area, there have been observations of a migrant raptor, but there are no official publications and research on migrant raptor in the Bukit 76 Kaliurang area, Yogyakarta. Therefore this research was conducted to know about migratory raptor in Yogyakarta. This research was conducted at Bukit 76 Kaliurang, Hargobinangun, Pakem, Yogyakarta. The research was conducted in December 2019-March 2020, July-August 2020, and October-November 2020. This research was conductes through observations in the morning at 07.00-11.00 WIB using birdwatching techniques and purposive methods. The results of this study recorded 1 species of migrant raptor, namely the Oriental Honey-buzzard (Pernis ptilorhynchus) and 2 species of resident raptors, namely the Crested Serpent Eagle (Spilornis cheela) and the Brahminy Kite (Haliastur indus).